Penerapan Sistem Pemberdayaan Masyarakat dalam Meningkatkan UMKM Kripik Gemblong di Kelurahan Sukamulya - Anggun, Putri (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This article discusses the Religious Moderation Community Service Program (KKN) activities carried out with the Community Empowerment System (SISDAMAS) approach to optimize community empowerment through the development of Gemblong Micro, Small and Medium Enterprises (MSMEs) in Sukamulya Village. There are 4 cycles that must be passed within 40 days. This is motivated by the fact that the businesses owned by the Sukamulya Village Community have not developed optimally. The limited amount of income has resulted in the development of a Loan Bank known as Bank Emok, so that the loan has the potential to harm the community. The 4 stages of the SISDAMAS KKN cycle are; cycle 1 is initial socialization; community meetings and social reflection; cycle 2 is social mapping and community organizing; cycle 3 is participatory planning and program synergy; and cycle 4 is program implementation, monitoring and evaluation. Community empowerment in improving Gemblong MSMEs in Sukamulya Village was carried out by students of the Religious Moderation KKN throughout Indonesia. With a program that involves the local community, it can certainly bring significant business benefits to the economy. The results of this program show an increase in MSME income and community awareness of the importance of economic independence, so it is expected to become a sustainable community empowerment model. The qualitative research methodology to discuss “Community Empowerment System in Improving Gemblong MSMEs in Sukamulya Village” was carried out using a descriptive approach, which aims to understand the phenomenon in depth through direct interaction with the research subject.